Ergonomic risk factors (ERFs) and prevalence of work-related musculoskeletal disorders (WMSDs) among solvent manufacturing workers in Shah Alam, Selangor - Ali, Nina Fatma; Roslan, Afiqah Nur Najihah (Universiti Putra Malaysia, 2024)
Introduction: Work-related musculoskeletal disorders (WMSDs) remain a significant occupational health issue across various industries, particularly in manufacturing, where ergonomic risk factors (ERFs) are prevalent. These disorders can lead to long-term discomfort, disability, and reduced productivity, making the identification and mitigation of ERFs critical for safeguarding workers' health. This study aimed to determine the prominent ERFs and the prevalence of WMSDs among workers in a solvent manufacturer in Shah Alam. Materials and methods: This study was conducted among 130 workers of a solvent manufacturer. The selection of workstations was done by a stratified sampling method. A self-administered Cornell Musculoskeletal Discomfort Questionnaire (CMDQ) was used to assess musculoskeletal discomfort among workers. In addition, Initial Ergonomic Assessment (IERA) was performed in all four departments to identify the prominent ERFs among the workers. The obtained data was analyzed using descriptive analysis, Chi-Square and Multiple Logistic Regression Results: Most of the participants were in the age range of 31 to 40 years old. Among the participants, the prominent ERFs were awkward posture, static and sustained work posture, forceful exertion and repetitive motion. The prevalence of WMSDs was 58.5%, with the highest was on the neck (40.8%) followed by right shoulder (28.5%), upper back (17.7%) and left shoulder (11.5%) respectively. The following ERFs were found to have a statistically significant association (p<0.05) with WMSDs: awkward posture (p= 0.000, OR=27.133), static and sustained work posture (p= 0.004, OR=2.985), forceful exertion (p= 0.033, OR=0.394) and repetitive motion (p= 0.033, OR=2.538). Conclusion: This study identified four prominent ERFs with neck being the most affected area with WMSDs among workers in the solvent manufacturing factory. The ERFs were highly associated with the prevalence of WMSDs which shows that it is critical to conduct further investigation and changes on the working methods to decrease the exposure level. An immediate intervention can be executed such as conducting ergonomics awareness training on proper working postures on a regular basis to ensure the reduction of ERFs among the workforces. It is recommended to use Rapid Upper Limb Assessment (RULA) to evaluate the exposure of individual workers to ERFs associated with upper extremity WMSDs.